THE IMPORTANCE OF VITAMINS AND MINERALS IN THE BODY OF WOMEN DURING THE CLIMACTERIC PERIOD (REPUBLIC OF UZBEKISTAN) - Saidova Gulbakhor Tursunalievna; Sayfullayeva Sevinch Gulomjon qizi (Journal Park Publishing, 2025)
Menopause is an inevitable period in a woman's life, when there is a restructuring of the hormonal system and the body as a whole. To make it easier to endure these processes, it is important to eat right during menopause. This will help the body cope with stress, as well as avoid diseases that often occur after menopause, for example, atherosclerosis, diabetes mellitus, obesity. For this reason, it is worth reviewing and, if necessary, making changes to the diet during menopause. Proper nutrition is, first of all, a balanced diet. Proteins, fats, and complex carbohydrates should be present in your diet.
Keywords: Menopause, menopausal syndrome, proper and rational nutrition, diseases.